(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1938)
The remains of Bronze Age occupation were stratified below Viking/medieval layers at Jarlshof and included stone dwelling, walls, hearths, middens and paved floors. Stone and quartz tools were found in large numbers. Other artefacts included bone tools, querns and a carved bone plaque.